UNESCO World Heritage Site of Lenggong Valley, Malaysia: A Review of its Contemporary Heritage Management. (3rd April 2015) - Mei Goh, Hsiao
Abstract : This article reviews contemporary heritage management through a systematically coded content analysis at one of Malaysia's UNESCO World Heritage Sites: the Archaeological Heritage of the Lenggong Valley (AHLV). It evaluates the competency of the preliminary Conservation Management Plan (CMP) of AHLV by looking at the accuracy of five distinctive dimensions of the CMP in conveying the information about the sites and management objectives: the legislation related to the heritage conservation and management; the action and implementation of the management strategies; the level of stakeholder's participation; and, finally, how the CMP integrates local values and ideas into management planning. The results show that contemporary heritage management planning at Lenggong Valley tends to prioritize the conservation of the archaeological values of the sites over other values (i.e. social, historical, and aesthetic values), and that planning has largely been in the hands of governmental agencies with limited involvement from local communities in the decision-making process.